2015
DOI: 10.3109/14756366.2015.1064406
|View full text |Cite
|
Sign up to set email alerts
|

The effects of some avermectins on bovine carbonic anhydrase enzyme

Abstract: Avermectins are effective agricultural pesticides and antiparasitic agents that are widely employed in the agricultural, veterinary and medical fields. The aim of this study was to investigate the inhibitory effects of selected avermectins including abamectin, doramectin, emamectin, eprinomectin, ivermectin and moxidectin that are used as drugs against a wide variety of internal and external mammalian parasites, on the carbonic anhydrase enzyme (CA, EC 4.2.1.1.) purified from fresh bovine erythrocyte. CA catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 79 publications
3
24
0
1
Order By: Relevance
“…Also, the utilization and development of new effective AChEIs is highly desired. Currently the most prescribed AChEIs are Tacrine, Galantamine, Rivastigmine, and Donepezil [55]. In the present study, AChE was very effectively inhibited by β-lactam derivatives 1 – 11 , with K i value in the range of 0.25 ± 0.019–1.13 ± 0.472 nM (Table 2) and calculated from Lineweaver-Burk plots [56].…”
Section: Resultssupporting
confidence: 51%
“…Also, the utilization and development of new effective AChEIs is highly desired. Currently the most prescribed AChEIs are Tacrine, Galantamine, Rivastigmine, and Donepezil [55]. In the present study, AChE was very effectively inhibited by β-lactam derivatives 1 – 11 , with K i value in the range of 0.25 ± 0.019–1.13 ± 0.472 nM (Table 2) and calculated from Lineweaver-Burk plots [56].…”
Section: Resultssupporting
confidence: 51%
“…Voriconazole is an antifungal medication used to treat a number of fungal infections, and its inhibitory effects against some metabolic enzymes are shown in Table and Figures . Previous research has clearly indicated that the inhibitory effect of Voriconazole against hCA I, hCA II, AChE, and α‐glycosidase is greater than or equal to that of morphine, antioxidant phenols, hydroquinone, taxifolin, spirobisnaphthalenes, caffeic acid phenethyl ester, rosmarinic acid, some hydroperoxides, alcohols and acetates, some ureas, eugenol derivatives, lignans, thioureas, flavonoids, synephrine and phenylephrine, avermectins, antibiotics, and TAC derivatives . The present study adds to this previous literature (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they have differences in tissue location and distribution; cytosolic (CA I–III, VII, and XIII), membrane bound (CA IV, IX, XII, XIV, XV), two mitochondrial (CA VA and VB), and one secreted (CA VI) in human saliva and serum. Also, there are three uncatalytic isoenzymes (CA VIII, X, and XI), which their functions are not yet fully understood .…”
Section: Introductionmentioning
confidence: 99%